2015
DOI: 10.1080/17445760.2015.1057589
|View full text |Cite
|
Sign up to set email alerts
|

Resource trading in cloud environments for utility maximisation using game theoretic modelling approach

Abstract: We develop a novel auction-based scheme for trading free processors in cloud computing environment. Our scheme allows clients to fairly compete for the offered processors. Second-price auction is used where each client bids for the processors. The client that makes the higher bid wins the auction and starts using the processors for executing its jobs. The winner pays the second highest bid. Maximising profit is the key objective for the cloud provider (CP). The optimisation problem of renting processors on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It was failed to reduce the BUR. A novel auction‐based scheme was developed in Alsarhan for operating free processors in CC environment. It does not improve the RT for trading processors.…”
Section: Related Workmentioning
confidence: 99%
“…It was failed to reduce the BUR. A novel auction‐based scheme was developed in Alsarhan for operating free processors in CC environment. It does not improve the RT for trading processors.…”
Section: Related Workmentioning
confidence: 99%
“…However, the QoS for clients depends on the allocated resources. A CP may trade anything from infrastructure [1,2,3] such as processors, memory, and Internet access. Despite many studies found in the literature under the umbrella of cloud computing, resource management in multiservice environments is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%